The Distribution of Capture Fisheries Based Small Pelagic - Mackerel Fish Species In Balikpapan Waters, East Kalimantan - Said Abdusysyahid; Sutrisno Anggoro; Azis Nur Bambang (Chemical Engineering Diponegoro University, 2014)
In the utilization of common property resource, long term balance in aquaculture is difficult to maintain as people trying to maximize their profit leading to considerable extensification. The objective of this research was to analyze the number of stock, production, and effort of Mackerel fish (Scomberomorus commersonii) resource based on bio-economic approach. Primary data was collected based on purposive sampling method where the respondents in this research were Small Pelagic fishers which determined deliberately due to specific consideration. Secondary data used in this research was obtained from several sources. Data production and effort (input or effort) was arranged in a time sequence according to the type of fishing gears and their targets of fishery resource being studied and then determined the value of CPUE (catch per unit effort). Mathematically, the input gear to be standardized is calculated from fishing power index multiplies with input (effort) of standardized gear. The result shows that the renewable capacity begins to decrease leading to a condition of biologically over fishing. Aside from that, the Mackerel fish resource in this area also experiences economically over fishing condition which indicated by higher economic calculation value and lower capture yield.